A light-emitting diode headlamp for motorcycles based on freeform micro-lenses. (June 2015) - Li, XF; Li, Y; Dong, JY; Chen, GD; Liang, C; Ge, P
We propose a light-emitting diode headlamp for motorcycles based on freeform micro-lenses. The freeform micro-lenses include a collimator and micro-lens structures. The rays emitted by the light-emitting diode source are first collimated and then redistributed by the microstructures. We make a point by point relationship between the light-emitting diode source and the target plane according to Economic Commission for Europe Regulation R113 revision 2. Simulation results show that the light pattern of our proposed headlamp could satisfy the requirements of the regulation. Illuminance on the test points, lines, and zones can fully meet the Economic Commission for Europe Regulation. The optical efficiency of our proposed headlamp could reach up to 90%, which is much higher than the traditional design.